Duloxetine in treating generalized anxiety disorder in adults: A meta‐analysis of published randomized, double‐blind, placebo‐controlled trials. (3rd August 2015) - Zhang, Yingli; Huang, Guoping; Yang, Shichang; Liang, Wei; Zhang, Lei; Wang, Changhong
Abstract: Introduction: We carried out a meta‐analysis of published randomized, double‐blind, placebo‐controlled trails to assess the efficacy and tolerability of duloxetine in treating generalized anxiety disorder (GAD). Methods: A literature search was conducted using PubMed, ISI Web of Science, Medline, Cochrane Central Register of Controlled Trials databases until October 2014. The search terms used were "anxiety or anxious or generalized anxiety disorder" and "duloxetine or Cymbalta." Meta‐analysis was conducted using Revman 5.1. A fixed‐effects model was carried out on the response rates, remission rates, and symptom improvement. Risk ratio (RR) and mean difference (MD) were calculated. The overall effect size was calculated with 95% confidence intervals (CIs). Results: Seven studies ( n = 2, 674) were found eligible for inclusion in analysis. Six studies provided data on response, which showed a significant difference between duloxetine and placebo ( n = 1, 975, RR = 1.48, 95% CI, 1.34–1.63). Remission rates revealed significant superiority of duloxetine ( n = 2, 399, RR = 1.60, 95% CI, 1.43–1.80). Change from baseline scores on Hamilton Rating Scale for Anxiety showed a reduction in anxiety symptoms to be significantly efficient for duloxetine ( n = 1, 135, MD = 3.34, 95% CI, 2.37–4.32). Duloxetine increased statistically Sheehan Disability Scale total score ( n = 1, 652, MD = 2.84, 95% CI, 2.08–3.60). The discontinuation of the duloxetine was not significantly different from that of the placebo. Conclusion: Duloxetine is moderately effective in treating GAD with improvement in overall function and well tolerability.